Use of Problem-Based Learning Methods in the Structure of Negotiation Texts for Class X Students of SMA Negeri 1 Sipirok - Aritonang, Devinna Riskiana; Dewi, Shoufi Nisma (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractThis research aims to determine the use of Problem Based Learning Methods in the structure of negotiation texts for class X students of SMA Negeri 1 Sipirok for the 2022-2023 academic year. This research method uses a qualitative method with a descriptive approach. The research informants consisted of: 36 class X SMA Negeri 1 Sipirok students and one teacher. The data analysis techniques used start from reducing data, presenting data, and drawing conclusions. The results of data analysis found that from the conceptual understanding of data I, there were only 16 students who did not complete. Student learning mastery in data I has an average score of 65.38 with a percentage of 70.22% in the